The influence of illness cognitions on disease course in rheumatoid arthritis : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Haddon, Glen (Massey University, 1995)
This study investigated the relation between a set of illness cognitions and certain other related psychological factors, and disease course in rheumatoid arthritis (RA). The illness cognitions were knowledge of RA, appraisal of one's current condition and expectations for the future, thinking style relative to one's RA, and locus of control. Measures of dispositional optimism/pessimism, negative affect, general psychological distress, and various demographic factors were also included. Disease course specifically excluded onset and outcome factors. It was operationalised as changes in difficulty with daily activities, changes in symptoms, speed of changes, remissions, and fluctuations. Participants comprised 82 RA sufferers, all members of the Arthritis Foundation who volunteered to complete a self-administered mailed questionnaire. Results showed that after controlling for the non-cognitive and demographic factors, the illness cognitions, as a set, had no influence on the course of RA. The results did demonstrate however, that the appraisal of present condition and expectations for the future cognition was meaningfully associated with RA disease course (on all disease course components) when its effect was assessed in isolation, and after taking into account the influence of the remaining cognitions. Some explanations are offered for the relative importance of this illness cognition together with possible reasons for the failure of the remaining cognitions to display any significant effect on disease course. The pervasiveness of the appraisal/expectations cognition and implications arising from the findings are discussed in terms of the roles of care-givers and their input towards more favourable disease course in RA.
Keywords: Rheumatoid arthritis; Rheumatoid arthritis patient psychology; Illness cognitions